Modified sodium vanadium phosphate positive electrode material as well as preparation method and application thereof
By modifying the sodium vanadium phosphate cathode material through anionic high-entropy doping and poly(p-phenylenevinyl) ethylene coating, the conductivity and stability issues were solved, achieving high-efficiency cycle and rate performance of sodium-ion batteries.
Patent Information
- Application Number
- CN202511778483.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-28
- Publication Date
- 2026-03-17
AI Technical Summary
Existing sodium vanadium phosphate cathode materials suffer from problems such as poor electronic conductivity, insufficient ion diffusion rate, poor structural stability, low compatibility with electrolytes, and easy dissolution of vanadium metal in sodium-ion batteries, which limit their application in long cycle life and high rate performance.
An anion-doped sodium vanadium phosphate/carbon cathode material was constructed by using anion high-entropy doping and poly(p-phenylenevinyl)ethylene coating. A dense organic conductive coating layer was formed on its surface to improve electronic conductivity and structural stability, suppress vanadium metal dissolution, and reduce side reactions between active materials and electrolyte.
It significantly improves the ionic conductivity, electronic conductivity, and structural stability of the cathode material, inhibits the dissolution of vanadium metal, improves cycle performance and rate performance, and enhances electrochemical performance.
Smart Images

Figure CN121687907A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of sodium battery technology, and in particular to a modified sodium vanadium phosphate cathode material, its preparation method, and its application. Background Technology
[0002] In the current process of social development, energy demand continues to grow, while the depletion of fossil fuels and environmental degradation are becoming increasingly prominent issues. Under these circumstances, wind and solar energy, as clean and renewable energy sources, have attracted widespread attention. However, wind and solar energy are intermittent and unstable, with high rates of curtailment, affecting their large-scale application. To rationally and efficiently utilize these two energy sources, the development of energy storage technology is urgently needed, with battery technology being the core. Compared to lithium, sodium is abundant, accounting for approximately 2.64% of the Earth's crust, and is widely distributed and inexpensive. Sodium-ion batteries, developed based on sodium, operate on a similar principle to lithium-ion batteries but possess more stable electrochemical performance, low-temperature performance, and safety, making them a promising next-generation, inexpensive, and environmentally friendly energy storage battery.
[0003] Sodium vanadium phosphate (PVP) with a NASICON structure has attracted much attention due to its high ionic conductivity, high operating voltage, excellent thermal stability and safety, and stable three-dimensional framework structure. However, PNP also has many drawbacks, such as poor electronic conductivity, insufficient ion diffusion rate, poor stability between the cathode material and the electrolyte, easy dissolution of vanadium metal during cycling, and the need to improve cycle stability. These limitations restrict its application in sodium-ion batteries with long cycle life and high rate performance. To address these issues, coating and doping techniques are commonly used to improve the electrochemical performance of PNP cathode materials. For example, simple carbon mixing and high-conductivity ion doping can improve electronic conductivity; high-entropy doping can improve the structural stability of the cathode material; and inorganic oxide coating can improve ionic conductivity and surface defects, thereby enhancing electrochemical cycle stability. However, existing doping and coating methods still have shortcomings. The coated and modified PNP cathode materials still suffer from low ionic and electronic conductivity, poor structural stability, low compatibility with electrolytes, and difficulty in suppressing vanadium metal dissolution.
[0004] Therefore, developing more advanced coating and doping modification technologies is crucial for promoting the further development of sodium vanadium phosphate batteries and realizing their widespread application in the energy storage field. Summary of the Invention
[0005] To address the aforementioned technical problems, this disclosure provides a modified sodium vanadium phosphate cathode material, its preparation method, and its application. The modified sodium vanadium phosphate cathode material provided by this disclosure not only enhances the ionic conductivity, electronic conductivity, and structural stability of the cathode material, but also suppresses the dissolution of vanadium metal in sodium vanadium phosphate and the side reactions between the cathode and the electrolyte, exhibiting excellent cycle performance and rate performance.
[0006] In a first aspect, this disclosure provides a modified sodium vanadium phosphate cathode material, the modified sodium vanadium phosphate cathode material comprising a core material and a poly(p-phenylene oxide) coating layer covering its surface; The core material comprises anion-doped sodium vanadium phosphate and carbon, wherein the anions include SiO4. 4- F - Cl - ,Br - P2O7 4- I - At least five of them.
[0007] This disclosure constructs anion-doped sodium vanadium phosphate / carbon cathode material by introducing carbon and multiple (at least five) anion doping elements into the sodium vanadium phosphate cathode material, and further coating its surface with poly(p-phenylene oxide) to form a dense and stable organic conductive coating layer. The synergistic high-entropy anion doping of carbon and the poly(p-phenylene oxide) coating layer not only improves the electronic conductivity of the cathode material but also enhances its structural stability, thereby improving the ion transport capacity of the cathode material. Simultaneously, the presence of high-entropy doping and the poly(p-phenylene oxide) coating layer can suppress the dissolution of V from sodium vanadium phosphate, reduce the direct contact between the active cathode and the electrolyte, suppress side reactions between the active material and the electrolyte, and reduce the interfacial resistance between the active material and the electrolyte, ultimately effectively improving the structural stability, cycle performance, and rate performance of the cathode material.
[0008] The following are preferred technical solutions of this disclosure, but are not intended to limit the technical solutions provided by this disclosure. The technical objectives and beneficial effects of this disclosure can be better achieved through the following technical solutions.
[0009] As a preferred technical solution of this disclosure, the chemical formula of the anion-doped sodium vanadium phosphate is Na. x V2(PO4) a (SiO4) b (P2O7) c F d Cl e Br f I g , among them, a+b+c+d+e+f+g=3, x+6=3a+4b+4c+d+e+f+g, 2.7≤a≤2.9, 0≤b<0.1, 0≤c<0.1, 0≤d<0.05, 0≤e<0.05, 0≤f<0.05, 0≤g<0.05.
[0010] Among them, a can be 2.7, 2.8, or 2.9, etc.; b can be 0, 0.05, or 0.09, etc.; c can be 0, 0.05, or 0.09, etc.; d can be 0, 0.02, or 0.04, etc.; e can be 0, 0.02, or 0.04, etc.; f can be 0, 0.02, or 0.04, etc.; g can be 0, 0.02, or 0.04, etc., but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0011] As a preferred technical solution of this disclosure, the chemical formula of the anion-doped sodium vanadium phosphate is Na. x V2(PO4) a (SiO4) b (P2O7) c F d Cl e Br f I g , among them, a+b+c+d+e+f+g=3, x+6=3a+4b+4c+d+e+f+g, 2.7≤a≤2.9, 0.0 5≤b<0.1, 0.05≤c<0.1, 0≤d<0.05, 0≤e<0.05, 0≤f<0.05, 0≤g<0.05.
[0012] As a preferred technical solution of this disclosure, the carbon content of the core material is 0.5-5% based on the total mass of the core material as 100%, such as 0.5%, 1%, 2%, 3%, 4% or 5%, etc., but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0013] When the carbon content and the content of each anion in the core material are within the above range, the electronic conductivity and structural stability of the cathode material can be improved more effectively, thereby improving the ion transport capacity of the cathode material more effectively.
[0014] Preferably, the carbon includes carbon materials obtained by high-temperature carbonization of organic or inorganic carbon sources.
[0015] As a preferred technical solution of this disclosure, based on the total mass of the modified sodium vanadium phosphate cathode material as 100%, the mass content of the poly(p-phenylenevinyl) coating layer is 0.5-5%, such as 0.5%, 1%, 2%, 3%, 4% or 5%, etc., but not limited to the listed values. Other unlisted values within this range are also applicable.
[0016] When the content of poly(p-phenylenevinyl) coating is within the above range, the coating structure is stable and dense, and it can more effectively suppress the side reactions between sodium vanadium phosphate cathode and electrolyte, as well as the dissolution of vanadium metal during cycling, thereby more effectively improving the cycle performance and rate performance of cathode material.
[0017] In a second aspect, this disclosure provides a method for preparing the modified sodium vanadium phosphate cathode material as described in the first aspect, the method comprising the following steps: (1) The vanadium source, sodium source, phosphorus source, anion source, carbon source and reducing agent are dissolved in the first solvent, and then sand-milled, dried and sintered in sequence to obtain the core material; (2) The core material, p-phenyleneethylene monomer, surfactant, initiator and second solvent are mixed and reacted to obtain modified sodium vanadium phosphate cathode material.
[0018] The preparation method described in this disclosure has a simple process flow, uniform coating layer distribution, and strong versatility, which helps to promote the industrialization and application of vanadium-based sodium-ion battery cathode materials.
[0019] As a preferred technical solution of this disclosure, the vanadium source in step (1) includes one or more of vanadium trioxide, vanadium pentoxide, ammonium metavanadate, vanadium oxychloride, vanadium tetrachloride, vanadium tribromide, or vanadium diiodide.
[0020] Preferably, the sodium source in step (1) includes one or more of sodium acetate, sodium carbonate, sodium bicarbonate, sodium orthosilicate, sodium fluoride, sodium chloride, sodium bromide, sodium pyrophosphate, sodium dihydrogen pyrophosphate, or sodium dihydrogen phosphate.
[0021] Preferably, the phosphorus source in step (1) includes one or more of sodium dihydrogen phosphate, ammonium dihydrogen phosphate, or diammonium hydrogen phosphate.
[0022] Preferably, the carbon source in step (1) includes one or more of glucose, sucrose, carbon nanofibers, carbon nanotubes, or graphene.
[0023] Preferably, the reducing agent in step (1) includes oxalic acid.
[0024] Preferably, in step (1), the first solvent includes deionized water.
[0025] Preferably, the anion source in step (1) is selected from vanadium oxychloride, vanadium tetrachloride, vanadium tribromide, vanadium diiodide, tetraethyl orthosilicate, sodium orthosilicate, sodium fluoride, sodium chloride, sodium bromide, sodium iodide, pyrophosphate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.
[0026] As a preferred technical solution of this disclosure, the grinding time in step (1) is 3-6 hours, such as 3 hours, 4 hours, 5 hours or 6 hours, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0027] Preferably, the drying in step (1) is spray drying, with an inlet air temperature of 150-220℃, such as 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃ or 220℃; and an outlet air temperature of 80-120℃, such as 80℃, 90℃, 100℃, 110℃ or 120℃, but not limited to the listed values. Other unlisted values within the above range are also applicable.
[0028] Preferably, the sintering temperature in step (1) is 700-850℃, such as 700℃, 720℃, 740℃, 760℃, 780℃, 800℃, 820℃ or 850℃, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0029] Preferably, the sintering time in step (1) is 6-15h, such as 6h, 8h, 10h, 13h or 15h, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0030] Preferably, the sintering in step (1) is carried out in an inert atmosphere.
[0031] As a preferred technical solution of this disclosure, the surfactant in step (2) includes sodium dodecyl sulfonate and / or polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer.
[0032] Preferably, the initiator in step (2) includes ammonium persulfate.
[0033] Preferably, in step (2), the second solvent comprises deionized water.
[0034] Preferably, the reaction time in step (2) is 10-24h, such as 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0035] Preferably, the preparation method further includes: washing and drying the product obtained after the reaction in step (2) in sequence, the drying temperature being 60-100℃, such as 60℃, 70℃, 80℃, 90℃ or 100℃, etc.; the drying time being 24-30h, such as 24h, 26h, 28h or 30h, etc., but not limited to the listed values, other unlisted values within the above range are also applicable.
[0036] Thirdly, this disclosure provides a modified sodium vanadium phosphate cathode material as described in the first aspect or prepared by the preparation method described in the second aspect.
[0037] Fourthly, this disclosure provides a sodium battery, the sodium battery comprising a positive electrode as described in the third aspect.
[0038] The technical solution provided in this disclosure has the following advantages compared with the prior art: (1) The modified sodium vanadium phosphate cathode material provided in this disclosure adopts a combination of anion high-entropy doping and composite coating, which can not only improve the electronic conductivity of the cathode material, suppress the dissolution of V metal elements, and ensure the structural stability of the cathode active material during cycling, but also isolate the direct contact between the electrode active material and the electrolyte, suppress the side reactions between the active material and the electrolyte, thereby reducing the accumulation of harmful by-products on the surface of the electrode material, ensuring the efficient transport of sodium ions at the interface, and ultimately improving the electrochemical performance of the cathode material.
[0039] (2) The modified sodium vanadium phosphate cathode material provided in this disclosure has a simple preparation process, uniform coating layer distribution, and strong versatility in preparation process, which helps to promote the industrialization and application of vanadium-based sodium ion battery cathode materials. Attached Figure Description
[0040] The accompanying drawings, which are incorporated in and form a part of this specification, illustrate embodiments consistent with this disclosure and, together with the description, serve to explain the principles of this disclosure.
[0041] To more clearly illustrate the technical solutions in the embodiments of this disclosure or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0042] Figure 1 The first charge-discharge curve of a half-cell assembled using the modified sodium vanadium phosphate cathode material prepared in Example 1 of this disclosure is shown in the figure. Figure 2 The graph shows the cycling performance of a half-cell assembled using the modified sodium vanadium phosphate cathode material prepared in Example 1 of this disclosure at a 1C rate. Figure 3 The diagram shows the rate performance of a half-cell assembled using the modified sodium vanadium phosphate cathode material prepared in Example 1 of this disclosure. Detailed Implementation
[0043] To better understand the above-mentioned objectives, features, and advantages of this disclosure, the solutions disclosed herein will be further described below. It should be noted that, unless otherwise specified, the embodiments and features described herein can be combined with each other.
[0044] Numerous specific details are set forth in the following description in order to provide a full understanding of this disclosure, but this disclosure may also be implemented in other ways different from those described herein; obviously, the embodiments in the specification are only some, and not all, of the embodiments of this disclosure.
[0045] Example 1 This embodiment provides a modified sodium vanadium phosphate cathode material and its preparation method, the preparation method including the following steps: (1) Mix 1.0 mol vanadium pentoxide (V2O5), 2.79 mol sodium dihydrogen phosphate (NaH2PO4), 0.07 mol sodium carbonate (Na2CO3), and 0.06 mol tetraethyl orthosilicate (C8H2PO4). 20 0.02 mol sodium fluoride (NaF), 0.03 mol sodium chloride (NaCl), 0.02 mol sodium bromide (NaBr), 0.08 mol pyrophosphate (H4P2O7), 1 mol oxalic acid (H2C2O4), and carbon nanotubes were dissolved in deionized water. The carbon nanotubes were added at a carbon composite content of 3 wt.% in the core material. The fully mixed material was milled for 4.0 h and then spray-dried. The inlet air temperature of the spray drying was 200℃ and the outlet air temperature was 100℃. The spray-dried material was sintered at 780℃ for 12 h under nitrogen protection to obtain the core material. (2) The core material obtained in step (1) is ultrasonically dispersed in deionized water to obtain a suspension solution; then, p-phenyleneethylene monomer is added dropwise to the above suspension solution, followed by the addition of polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer (F127) and ammonium persulfate. The mixture is stirred thoroughly for 20 hours, then washed with deionized water, and then dried at 70°C for 30 hours to obtain modified sodium vanadium phosphate cathode material, wherein the coating amount of poly(p-phenyleneethylene) accounts for 2 wt.% of the mass of the modified sodium vanadium phosphate cathode material.
[0046] Example 2 This embodiment provides a modified sodium vanadium phosphate cathode material and its preparation method, the preparation method including the following steps: (1) Mix 1.0 mol vanadium trioxide (V2O3), 2.43 mol sodium bicarbonate (NaHCO3), 2.81 mol ammonium dihydrogen phosphate (NH4H2PO4), 0.06 mol sodium orthosilicate (Na4SiO4), 0.04 mol sodium fluoride (NaF), 0.02 mol sodium chloride (NaCl), 0.01 mol sodium bromide (NaBr), 0.06 mol sodium pyrophosphate (Na4P2O7), 1 mol oxalic acid (H2C2O4), and glucose (C6H2O) 12 O6) is dissolved in deionized water; glucose is added at a mass of 2 wt.% of the carbon composite content in the core material. The fully mixed material is sand-milled for 3.5 hours and then spray-dried. The inlet air temperature of the spray drying is 210℃ and the outlet air temperature is 90℃. The spray-dried material is sintered at 850℃ for 8 hours in a nitrogen protective atmosphere to obtain the core material. (2) The core material obtained in step (1) is ultrasonically dispersed in deionized water to obtain a suspension solution; then, p-phenyleneethylene monomer is added dropwise to the above suspension solution, followed by the addition of polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer (F127) and ammonium persulfate, and stirred thoroughly for 15 h. Then, it is washed with deionized water and dried at 100 °C for 25 h to obtain modified sodium vanadium phosphate cathode material, wherein the coating amount of poly(p-phenyleneethylene) accounts for 4 wt.% of the mass of modified sodium vanadium phosphate cathode material.
[0047] Example 3 This embodiment provides a modified sodium vanadium phosphate cathode material and its preparation method, the preparation method including the following steps: (1) 1.985 mol ammonium metavanadate (NH4VO3), 2.46 mol sodium acetate (CH3COONa), 2.75 mol ammonium dihydrogen phosphate (NH4H2PO4), 0.015 mol vanadium diiodide (VI2), 0.05 mol sodium orthosilicate (Na4SiO4), 0.03 mol sodium fluoride (NaF), 0.05 mol sodium chloride (NaCl), 0.09 mol sodium dihydrogen pyrophosphate (Na2H2P2O7), 1 mol oxalic acid (H2C2O4), and sucrose (C 12 H 22 O 11 The mixture is dissolved in deionized water; sucrose is added at a rate of 4 wt.% of the carbon composite content in the core material. The fully mixed material is then sand-milled for 5.5 hours and spray-dried. The inlet air temperature of the spray dryer is 170°C and the outlet air temperature is 80°C. The spray-dried material is then sintered at 750°C for 14 hours under nitrogen protection to obtain the core material. (2) The core material obtained in step (1) is ultrasonically dispersed in deionized water to obtain a suspension solution; then, p-phenyleneethylene monomer is added dropwise to the above suspension solution, followed by the addition of polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer (F127) and ammonium persulfate, and stirred thoroughly for 12 hours. Then, it is washed with deionized water and dried at 100°C for 25 hours to obtain modified sodium vanadium phosphate cathode material, wherein the coating amount of poly(p-phenyleneethylene) accounts for 4.5 wt.% of the mass of modified sodium vanadium phosphate cathode material.
[0048] Example 4 This embodiment provides a modified sodium vanadium phosphate cathode material and its preparation method, the preparation method including the following steps: (1) 0.98 mol vanadium pentoxide (V2O5), 2.88 mol sodium acetate (CH3COONa), 2.89 mol diammonium hydrogen phosphate ((NH4)2HPO4), 0.005 mol vanadium oxychloride (VOCl3), 0.005 mol vanadium tribromide (VBr3), 0.01 mol sodium fluoride (NaF), 0.02 mol sodium iodide (NaI), 0.05 mol sodium pyrophosphate (Na4P2O7), 1 mol oxalic acid (H2C2O4) and graphene were mixed and dissolved in deionized water; wherein, the mass of graphene was added according to the carbon composite content ratio of 1wt.% in the core material. After the fully mixed material was sand milled for 5.0h, it was spray dried. The inlet air temperature of the spray drying was 180℃ and the outlet air temperature was 90℃. The spray-dried material was sintered at 720℃ for 10h in nitrogen protective gas to obtain the core material. (2) The core material obtained in step (1) is ultrasonically dispersed in deionized water to obtain a suspension solution; then, p-phenyleneethylene monomer is added dropwise to the above suspension solution, followed by the addition of polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer (F127) and ammonium persulfate, and stirred thoroughly for 22 hours. Then, it is washed with deionized water and dried at 90°C for 25 hours to obtain modified sodium vanadium phosphate cathode material, wherein the coating amount of poly(p-phenyleneethylene) accounts for 3 wt.% of the mass of modified sodium vanadium phosphate cathode material.
[0049] Example 5 This embodiment provides a modified sodium vanadium phosphate cathode material and its preparation method, the preparation method including the following steps: (1) 1.96 mol ammonium metavanadate (NH4VO3), 2.21 mol sodium acetate (CH3COONa), 2.72 mol diammonium hydrogen phosphate ((NH4)2HPO4), 0.09 mol sodium orthosilicate (Na4SiO4), 0.005 mol vanadium tetrachloride (VCl4), 0.01 mol vanadium tribromide (VBr3), 0.025 mol vanadium diiodide (VI2), 0.09 mol sodium pyrophosphate (Na4P2O7), 1 Oxalic acid (H2C2O4) and carbon nanofibers were mixed and dissolved in deionized water. The carbon nanofibers were added at a mass ratio of 4.5 wt.% of the carbon composite in the core material. The fully mixed material was milled for 3.0 h and then spray-dried. The inlet air temperature of the spray drying was 220℃ and the outlet air temperature was 110℃. The spray-dried material was sintered at 800℃ for 10 h under nitrogen protection to obtain the core material. (2) The core material obtained in step (1) is ultrasonically dispersed in deionized water to obtain a suspension solution; then, p-phenyleneethylene monomer is added dropwise to the above suspension solution, followed by the addition of polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer (F127) and ammonium persulfate, and stirred thoroughly for 18 hours. Then, it is washed with deionized water and dried at 85°C for 28 hours to obtain modified sodium vanadium phosphate cathode material, wherein the coating amount of poly(p-phenyleneethylene) accounts for 1 wt.% of the mass of modified sodium vanadium phosphate cathode material.
[0050] Example 6 This comparative example provides a high-entropy doped sodium vanadium phosphate cathode material and its preparation method. The preparation method is the same as that in Example 1, except that the coating amount of polyethylene terephthalate in step (2) accounts for 8 wt.% of the mass of the modified sodium vanadium phosphate cathode material.
[0051] Comparative Example 1 This comparative example provides a modified sodium vanadium phosphate cathode material and its preparation method. The preparation method is the same as that in Example 1, except that an anion source is not added in step (1).
[0052] Comparative Example 2 This comparative example provides a modified sodium vanadium phosphate cathode material and its preparation method. The preparation method is the same as that in Example 1, except that pyrophosphate (H4P2O7) is not added in step (1), and tetraethyl orthosilicate (C8H2O7) is used. 20 The amount of O4Si added was changed to 0.14 mol.
[0053] Comparative Example 3 This comparative example provides a modified sodium vanadium phosphate cathode material and its preparation method. The preparation method is the same as that in Example 1, except that sodium fluoride (NaF) is not added in step (1), and the amount of sodium chloride (NaCl) added is 0.05 mol.
[0054] Comparative Example 4 This comparative example provides a modified sodium vanadium phosphate cathode material and its preparation method. The preparation method is the same as that in Example 1, except that sodium chloride (NaCl) is not added in step (1), and the amount of sodium bromide (NaBr) added is 0.05 mol.
[0055] Comparative Example 5 This comparative example provides a modified sodium vanadium phosphate cathode material and its preparation method. The preparation method is the same as that in Example 1, except that sodium bromide (NaBr) is not added in step (1), and the amount of sodium fluoride (NaF) added is 0.04 mol.
[0056] Comparative Example 6 This comparative example provides a high-entropy doped sodium vanadium phosphate cathode material and its preparation method. The preparation method is the same as that in Example 1, except that: it does not coat poly(p-phenylene oxide), that is, it does not perform step (2).
[0057] Comparative Example 7 This comparative example provides a high-entropy doped sodium vanadium phosphate cathode material and its preparation method. The preparation method is the same as that in Example 1, except that the p-phenylenevinyl ether monomer in step (2) is replaced with polydopamine.
[0058] Performance testing Sodium battery used for testing: Preparation of a test sodium battery: The positive electrode materials prepared in the examples and comparative examples were used as positive electrode active materials, and were mixed with SuperP conductive carbon and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 to obtain a positive electrode active slurry. The slurry was then coated onto an aluminum foil current collector to form a positive electrode sheet, with an active material layer density of 4-5 mg / cm³. 2 A button cell was assembled in a glove box under a high-purity argon atmosphere using a sodium metal sheet as the counter electrode, 1M NaClO4 dissolved in propylene carbonate solution, 5 vol% fluoroethylene carbonate as the electrolyte, and glass fiber as the separator.
[0059] Electrochemical performance tests were performed on the assembled coin cells, and the test results are as follows: Figure 1-3 And as shown in Table 1. Among them, Figure 1The first charge-discharge curve of the coin cell assembled using the modified sodium vanadium phosphate cathode material prepared in Example 1 at a rate of 0.1C. Figure 2 The graph shows the cycling performance of a coin cell assembled using the coated modified high-entropy doped sodium vanadium phosphate cathode material prepared in Example 1 at a 1C rate. Figure 3 The graph shows the rate performance of a coin cell assembled using the modified sodium vanadium phosphate cathode material prepared in Example 1.
[0060] Table 1
[0061] From Table 1 and Figure 1-3 It can be observed that the coin cells assembled using the modified sodium vanadium phosphate cathode material prepared in this disclosure have excellent rate performance and cycle performance.
[0062] A comparison of Examples 1-6 and Comparative Examples 1-7 reveals that high-entropy doping and a dense, stable coating layer can not only effectively enhance the ionic conductivity, electronic conductivity, and structural stability of the cathode material, but also suppress the side reactions between the sodium vanadium phosphate cathode and the electrolyte, as well as the dissolution of vanadium metal during cycling, thus effectively improving the cycling stability and rate performance of the cathode material.
[0063] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0064] The above description is merely a specific embodiment of this disclosure, enabling those skilled in the art to understand or implement it. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this disclosure. Therefore, this disclosure is not to be limited to the embodiments described herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A modified sodium vanadium phosphate cathode material, characterized in that, The modified sodium vanadium phosphate positive electrode material comprises a core material and a poly-p-phenylenevinylene coating layer coated on the surface of the core material. The core material includes a mixture of anion-doped sodium vanadium phosphate and carbon, the anion including at least five of SiO4 4- , F - , Cl - , Br - , P2O7 4- , I - . 2.The modified sodium vanadium phosphate positive electrode material of claim 1, characterized in that, The chemical formula of the anion-doped sodium vanadium phosphate is Na x V2(PO4) a (SiO4) b (P2O7) c F d Cl e Br f I g Wherein, a+b+c+d+e+f+g=3, x+6=3a+4b+4c+d+e+f+g, 2.7≤a≤2.9, 0≤b<0.1, 0≤c<0.1, 0≤d<0.05, 0≤e<0.05, 0≤f<0.05, 0≤g<0.
05. Preferably, the anion-doped sodium vanadium phosphate has the chemical formula Na x V2(PO4) a (SiO4) b (P2O7) c F d Cl e Br f I g wherein a+b+c+d+e+f+g=3, x+6=3a+4b+4c+d+e+f+g, 2.7≤a≤2.9, 0.05≤b<0.1, 0.05≤c<0.1, 0≤d<0.05, 0≤e<0.05, 0≤f<0.05, 0≤g<0.
05. 3.The modified sodium vanadium phosphate positive electrode material according to claim 1 or 2, characterized in that, The mass content of carbon is 0.5-5% based on the total mass of the core material.
4. The modified sodium vanadium phosphate positive electrode material according to any one of claims 1-3, characterized in that, The mass content of the poly-p-phenylenevinylene coating layer is 0.5-5% based on the total mass of the modified sodium vanadium phosphate positive electrode material.
5. A method for preparing the modified sodium vanadium phosphate cathode material according to any one of claims 1-4, characterized in that, The preparation method comprises the following steps: (1) dissolving a vanadium source, a sodium source, a phosphorus source, an anion source, a carbon source and a reducing agent in a first solvent, and sequentially performing sand milling, drying and sintering to obtain a core material; (2) mixing the core material, a p-phenylenevinylene monomer, a surfactant, an initiator and a second solvent to perform a reaction, and obtaining a modified sodium vanadium phosphate positive electrode material after the reaction.
6. The production method according to claim 5, characterized by, The vanadium source in step (1) comprises one or more of vanadium trioxide, vanadium pentoxide, ammonium metavanadate, vanadyl chloride, vanadium tetrachloride, vanadium tribromide or vanadium diiodide; Preferably, the sodium source in step (1) comprises one or more of sodium acetate, sodium carbonate, sodium bicarbonate, sodium orthosilicate, sodium fluoride, sodium chloride, sodium bromide, sodium pyrophosphate, sodium dihydrogen pyrophosphate or sodium dihydrogen phosphate; Preferably, the phosphorus source in step (1) comprises one or more of sodium dihydrogen phosphate, ammonium dihydrogen phosphate or di-ammonium hydrogen phosphate; Preferably, the carbon source in step (1) comprises one or more of glucose, sucrose, carbon nanofiber, carbon nanotube or graphene; Preferably, the reducing agent in step (1) comprises oxalic acid; Preferably, the first solvent in step (1) comprises deionized water; Preferably, the anion source in step (1) is selected from vanadyl chloride, vanadium tetrachloride, vanadium tribromide, vanadium diiodide, tetraethyl orthosilicate, sodium orthosilicate, sodium fluoride, sodium chloride, sodium bromide, sodium iodide, pyrophosphoric acid, sodium pyrophosphate and sodium dihydrogen pyrophosphate.
7. The production method according to claim 5 or 6, characterized by, The sand milling time in step (1) is 3-6h; Preferably, the drying in step (1) is spray drying, the inlet air temperature is 150-220℃, and the outlet air temperature is 80-120℃; Preferably, the sintering temperature in step (1) is 700-850℃; Preferably, the sintering time in step (1) is 6-15h; Preferably, the sintering in step (1) is performed in an inert atmosphere.
8. The method of any one of claims 5-7, wherein, The surfactant in step (2) comprises sodium dodecyl sulfonate and / or polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer; Preferably, the initiator in step (2) comprises ammonium persulfate; Preferably, the second solvent in step (2) comprises deionized water; Preferably, the reaction time in step (2) is 10-24h; Preferably, the preparation method further comprises: sequentially performing washing and drying on the product obtained after the reaction in step (2), and the drying temperature is 60-100℃ and the drying time is 24-30h.
9. A positive electrode sheet characterized by comprising: The positive electrode plate comprises the modified sodium vanadium phosphate positive electrode material according to any one of claims 1-4 4 The modified sodium vanadium phosphate positive electrode material according to any one of claims 1-4 or the positive electrode plate according to claim 5 The modified sodium vanadium phosphate positive electrode material prepared by the preparation method in any one of the preceding claims.
10. A sodium battery, characterized by, The sodium battery comprises the positive electrode sheet in claim 9.